Double Interphalangeal Joint Dislocation of the Finger in Adolescent Athletes: A Review of Two Cases and the Relevant Literature. (15th March 2021) - Vasiliadis, Angelo V.; Maris, Alexandros; Tsatlidou, Maria; Bray, Edward D. R.; Metaxiotis, Dimitrios
Abstract : Double interphalangeal joint dislocation of the same finger is a rare condition. We report two cases of adolescent athletes with distal and proximal interphalangeal joint dislocation. The diagnosis was confirmed with plain radiograph, while anatomical reduction was easily obtained with gentle longitudinal traction. A simple immobilization of the injured finger was applied by buddy taping for two weeks. Early mobilization as tolerated was recommended, and they have made a full return to their previous status of activities within 5 months. We also provide a review of the literature detailing demographic characteristics, cause and mechanism of injury with associated injuries, treatment options, and functional outcomes in this population.